Livros e leitura na cidade de Pelotas RS no final do século XIX: um estudo através dos jornais pelotenses (1875-1900) - Gonçalves, Renata Braz (2010)
Based on a qualitative approach, this documental research has had as an objective to identify reading representations that were registered by the press from Pelotas-RS, in the end of the XIX century. The corpus analysis has been composed by news, ads, comments and literary texts, all published in the newspapers (commercial, literary, political, news-like or ludicrous) circulating in Pelotas between 1875 and 1900, as well as regulations and minutes from literary groups and from the Pelotense Public Library. In order to provide support for this research, we have tried to approach the concepts and the methodologies used and spread by the reading historians who work under the perspective of Cultural History, emphasizing Roger Chartier, who presents the Representation and the Appropriations as central concepts. In order to do so, aspects of production and circulation of reading pieces - typography, libraries, authors and editors - have been identified in Pelotas, in the XIX century. Readers´ representation that could be classified by gender: men and women, age, children and adults have also been stated. The analysis has also allowed the description of reading events and spaces as: The Pelotense Public Library, literary associations and the saraus (musical and literary gatherings) that happened in these places. Apart from that, the reading representations in thenewspapers written speeches (in which it was possible to understand reading as instruction, need, danger and salvation, as well as to verify a straight relationwith literacy), have been identified